2021
DOI: 10.1111/jpc.15495
|View full text |Cite
|
Sign up to set email alerts
|

CHILDREN WITH CYSTIC FIBROSIS HOSPITALISED WITH COVID‐19: MULTICENTRE EXPERIENCE

Abstract: The effects of telemedicine on asthma control and patients' quality of life in adults: A systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Moreover, decreased TMPRSS2 would reduce SARS-CoV-2 entry into airway epithelial cells. 26,27 In the current study, no cases were admitted to ICU or died because of COVID-19. This could have been due to lower ACE expression in these children and the fact that children with a chronic lung disease such as CF and their parents are more careful about hygiene because of concerns about serious disease, and these precautions were significantly increased during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, decreased TMPRSS2 would reduce SARS-CoV-2 entry into airway epithelial cells. 26,27 In the current study, no cases were admitted to ICU or died because of COVID-19. This could have been due to lower ACE expression in these children and the fact that children with a chronic lung disease such as CF and their parents are more careful about hygiene because of concerns about serious disease, and these precautions were significantly increased during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 80%
“…A total of 31 papers published as observational studies reported an association of COVID-19 in patients with CF [ 18 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] ( Table 1 ). These studies comprised 661,386 patients in total, including children, adults, and elderly age groups.…”
Section: Resultsmentioning
confidence: 99%
“…However, only 19,150 (2.9%) patients were diagnosed with CF and, from these patients, 2523 (0.4%) were diagnosed with both CF and COVID-19. Regarding patients with CF and COVID-19, the sex proportion was (female/male) 1207/1167 [ 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 45 , 47 , 48 , 49 , 50 ]. Some publications [ 21 , 26 , 35 , 40 , 46 ] did not report the sex of the patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there was no reported data in the Arab Gulf region that reflects the pediatric CF population. However, Alyazidi et al 30 reported COVID-19 infection in three children with CF who required hospitalization during the first year of the COVID-19 wave in three main pediatric hospitals in Oman. Only one patient with moderate-severe CF-related lung disease required respiratory support with non-invasive ventilation.…”
Section: Discussionmentioning
confidence: 99%